THE MOST SUITABLE MOBILE RFID READER SELECTION BY USING INTERVAL TYPE-2 FUZZY TOPSIS METHOD - Yıldız, Aytaç; Karakoyun, Fatih; Parlak, Ismail Enes (Yildiz Technical Univ, 2018)
The novelties, innovations and ease of practical applications that the technology brings as it develops have become dispensable parts of our daily life. RFID technology, one of these novelties, forms the basis for new coding, storage and transmission systems; as well as helping businesses to solve the issues that they encounter in controlling data or the troubles faced due to lack of information. RFID applications in supply chain management insure several advantages; providing more accurate and faster communication, ensuring traceability on dealers networks and developing control mechanisms by ensuring real-time information transmission between logistics activities and supply chain management. RFID readers, one of the components of the RFID system, are the cores of RFID systems, and they all have unique and distinct properties that distinguish from each other. Prior to the creation of an RFID system, the selection of the suitable RFID readers that meet all the needs is the leading important issue. In this study, the aim is to select the most suitable mobile RFID reader for a business that aims to organize warehouse transactions in supply chain management and reduce the errors in shipping operations. Since there are multiple criteria in selection of the RFID readers, the problem is considered as a multi-criteria decision making problem and the Interval Type-2 Fuzzy TOPSIS method, which uses type-2 fuzzy sets, is used for solution, as it is more effective in solving the uncertainties. After determining the effective criteria and alternatives in selection of mobile RFID reader, by adopting the steps of the method, "RFID Reader-2" which is superior to other alternatives in terms of "Memory", "Read Distance" and "Drop Spec.", has been chosen as the most suitable mobile RFID reader. Finally, the results that are obtained in the study are evaluated and suggestions for future studies are made.
Keywords: RFID; type-2 fuzzy sets; fuzzy TOPSIS; supply chain